Wireless MRI Colonoscopy for Sensitive Imaging of Vascular Walls - Zeng, Xianchun (Sci Rep, 2017)
A Wireless Amplified NMR Detector (WAND) with cylindrical symmetry has been fabricated and non-surgically inserted into a rodent lower digestive track to improve the imaging quality of deep-lying vessels inside the abdominal cavity. This symmetric detector has a compact design using two end-rings and two vertical legs to create two orthogonal resonance modes. Based on the principle of parametric amplification, the detector can harvest wireless pumping power with its end-rings and amplify Magnetic Resonance signals induced on its vertical legs. With good longitudinal and azimuthal homogeneity, the WAND can achieve up to 21-times sensitivity gain over a standard external detector for immediately adjacent regions, and at least 5-times sensitivity gain for regions separated by one diameter away from the detector’s cylindrical surface. The WAND can approach the region of interest through the lower digestive track, similar as a colonoscopy detector. But unlike an optical camera, the amplified MR detector can “see” across intestinal boundaries and clearly identify the walls of bifurcated vessels that are susceptible to atherosclerotic lesions. In addition to vascular wall imaging, this detector may also be used as a swallowable capsule to enhance the detection sensitivity of deep-lying organs near the digestive track.